2019
DOI: 10.1109/access.2019.2937180
|View full text |Cite
|
Sign up to set email alerts
|

Stability Enhancement and Direct Speed Control of DFIG Inertia Emulation Control Strategy

Abstract: With the increasing penetration of renewable energy generators in power grid, traditional vector control (VC) strategy for double fed induction generator (DFIG) is unable to provide extra active power support to grid because DIFG inertia is made decoupled from grid frequency fluctuations. To solve this problem, Virtual Synchronous Generator (VSG) control strategy as well as Inertial Synchronization Control (ISynC) strategy are proposed for DFIG rotor side converter (RSC) and grid side converter (GSC) respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The reference voltage of the converter is kept constant over each sampling interval, so the converter can be assumed to be a ZOH circuit [13], [14], [17], [27], [33], [35]. As a result, the discrete-time model can be obtained through the ZOH method to (1), which can be expressed as follows:…”
Section: System Modeling and Current Controllers For Gccs In The Srfmentioning
confidence: 99%
See 4 more Smart Citations
“…The reference voltage of the converter is kept constant over each sampling interval, so the converter can be assumed to be a ZOH circuit [13], [14], [17], [27], [33], [35]. As a result, the discrete-time model can be obtained through the ZOH method to (1), which can be expressed as follows:…”
Section: System Modeling and Current Controllers For Gccs In The Srfmentioning
confidence: 99%
“…Similarly, the root locus of current loop, which is plotted by varying the controller gain k in (8), can be obtained, as shown in Fig.5(a). The two trajectories initiated from p 1,2 ol , are noted as 1 and 2 , respectively. It can be observed that with the increasing of k, trajectories 1 and 2 meet at the point of ''A'' and then depart in the opposite direction, before which the system is over damped.…”
Section: Tuning Of Dcpi Based On Critical Damping In the Discretmentioning
confidence: 99%
See 3 more Smart Citations